The Reality of Training and its Needs, for Production Managers of the Footwear, Leather and Manufactures Sector in the Metropolitan Area of Cúcuta (2019)
The research identified the reality of the training and its needs, in the managers of industrial production of footwear, leather and leather goods in the metropolitan area of Cúcuta. The study was addressed by applying a validated and reliable, which led to a current profile for the 20 managerial skills sector production managers. The areas with greater training received were: inventory management, supervisory skills, improving product quality and design of new products. The most commonly used types of training are lectures, seminars and short courses and the institutions they support are external consultants and other public or private institutions. The current profile allowed to identify training needs in the technical skills of planning, scheduling, production control and inventory control through software tools. The human skills include capacity building of teamwork, negotiation, leadership and management tools to communicate effectively. Finally, conceptual skills required management methods to collect information.